Lathrolestes pleuralis Thomson 1883 ... - Reshchikov, Alexey (Zenodo, 2012)
Lathrolestes pleuralis (Thomson, 1883) Figs 77, 78 Material: female, Russia, Chita reg., Savinsky Ingoda st., 14.viii.1970, D. Kasparyan; female, Russia, Kamchatka, Kronotsky res., geyser valley, 17.viii.1985, I. Kerzhner; female, Russia, Primorsky Kray, 15km. NW Partizansk, Brovnichi, forest, 29.vi.1996, S. Belokobilskij; 6females, Russia, Primorsky Kray, 30km. SE Ussuriysk, forest, Ussuriysky res., 10–11.vi.1993, S. Belokobilskij; female, Russia, Primorsky Kray, Spassk, 10– 12.vii.1993, S. Belokobilskij; female, Russia, Primorsky Kray, Spassk, 25.vi.1981, S. Belokobilskij; 10females, 10males, Russia, Khabarovsky Kray, Khekhtsyr, 18th km., larch forest, 08.vi.1983, D. Kasparyan; 3female, male, Russia, Khabarovsky Kray, Khekhtsyr, 17th km., deciduous forest, 03.vii.1983, D. Kasparyan; female, Russia, Primorsky Kray, 5km. W Anisimovka, forest, 6–9.viii.1993, S. Belokobilskij; 2females, male, Russia, Khabarovsky Kray, Khekhtsyr, Levaya river, coniferous-deciduous forest, 02.vii.1983, D. Kasparyan; 5female, ... : Published as part of Reshchikov, Alexey, 2012, Review and key to Russian Far East Lathrolestes (Hymenoptera, Ichneumonidae), pp. 1-32 in Zootaxa 3414 on page 32, DOI: 10.5281/zenodo.281927 ...